2020
DOI: 10.1177/2050312120901559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of range of motion on muscle development during resistance training interventions: A systematic review

Abstract: The purpose of this study was to systematically review the literature as to the effects of performing exercise with a full versus partial range of motion (ROM) during dynamic, longitudinal resistance training (RT) programs on changes in muscle hypertrophy. Based on the available literature, we aimed to draw evidence-based recommendations for RT prescription. Six studies were identified as meeting inclusion criteria: four of these studies involved RT for the lower limbs while the other two focused on the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
1
35
0
2
Order By: Relevance
“…One of the basic differentiating factors during the bench press exercise with the CB and SB is the ROM. Previous studies showed that changes in the ROM impact on acute responses as well as chronic adaptive changes (Bloomquist et al, 2013;Pallarés et al, 2020;Schoenfeld and Grgic, 2020). The changes in the ROM during long-term resistance training impact movement velocity and power output, as well as the utilization of elastic energy derived in the stretch -shortening cycle (Martínez-Cava et al, 2019a;Pallarés et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the basic differentiating factors during the bench press exercise with the CB and SB is the ROM. Previous studies showed that changes in the ROM impact on acute responses as well as chronic adaptive changes (Bloomquist et al, 2013;Pallarés et al, 2020;Schoenfeld and Grgic, 2020). The changes in the ROM during long-term resistance training impact movement velocity and power output, as well as the utilization of elastic energy derived in the stretch -shortening cycle (Martínez-Cava et al, 2019a;Pallarés et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training is a common form of exercise for athletes and physically active people. A large and growing body of research has investigated the influence of the range of motion (ROM) during different resistance exercises and the specific neuromuscular adaptations they induce (Hartmann et al, 2012;Bloomquist et al, 2013;Martínez-Cava et al, 2019;Pallarés et al, 2020;Schoenfeld and Grgic, 2020). The available research has analyzed the effects of full (allowed by the standard barbell) or partial ROM during the bench press (BP) exercise on acute (Krzysztofik et al, 2020) as well as chronic changes in performance (Martínez-Cava et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The available research has analyzed the effects of full (allowed by the standard barbell) or partial ROM during the bench press (BP) exercise on acute (Krzysztofik et al, 2020) as well as chronic changes in performance (Martínez-Cava et al, 2019). Moreover, the manipulation of the ROM during resistance exercises is a strategy commonly used among strength-trained athletes according to the principle of specificity (Schoenfeld and Grgic, 2020). However, recent evidence indicates that performing resistance exercises with a full ROM provides a greater stimulus, and leads to greater performance improvements in comparison to lifting with a limited ROM (Hartmann et al, 2012;Bloomquist et al, 2013;Martínez-Cava et al, 2019;Pallarés et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Strength is defined as the maximum force or torque a muscle or muscle-group can produce given a specific predetermined velocity (13)(14)(15). Therein, task-specific conditions, such as the speed and type of contraction and the length of the muscle during contraction, all codetermine the torque generated (14,16,17). The American College of Sports Medicine (ACSM) exemplifies strength as a 1 repetition maximum (1RM) squat (16).…”
Section: Introductionmentioning
confidence: 99%